The definition of potential infiltration areas in Guaratingueta watershed, Paraiba do Sul Basin, Southeastern Brazil: an integrated approach using physical and land-use elements - Soares, Paulo Valladares; Pereira, Sueli Yoshinaga; Simoes, Silvio Jorge C. [UNESP]; Bernardes, George de Paula [UNESP]; Barbosa, Sergio Augusto; Trannin, Isabel Cristina B. [UNESP] (Springer, 2012)
This work describes the methodological approach used for mapping the potential infiltration areas of the Guaratingueta watershed (160 km(2)), situated in Southeastern Brazil. The method is considered a qualitative approach, which takes into account thematic maps (geology, pedology, geomorphology, and land use/land cover) and the precipitation spatial distribution. A group of experts in Earth Sciences and Geotechnical Engineering has applied an infiltration potential scale factor that ranges from 5 (highest influence) to 1 (lowest influence). The final infiltration map was produced using several ArcGIS((R)) tools. The results showed that the most suitable (very high) infiltration areas represent only around 7% of the watershed area, which are associated with smooth and gentle hills, fluvial Tertiary sediments and yellow oxisols. However, growing impacts caused by land farming and urban developments require urgent planning for this region. Areas with high to moderate capacity of infiltration represent around 56% of the watershed and are found in the domain of igneous-metamorphic rocks associated with steep hill-slopes and relatively well-preserved forest fragments. This region requires a land-use strategy, such as reforestation programs, in order to increase the infiltration capacity of the watershed.
Keywords: Infiltration; Physical elements; Precipitation; Geographic information system; Southeastern Brazil